Evaluation of the Survival Rate and Bone Loss of Implants with Various Lengths - AR. Rokn; H. Noorani; R. Afzalifar (Tehran University of Medical Sciences, 2006)
Statement of Problem: The replacement of missing teeth with implant-associated restorations has become a widely used treatment modality in recent years. The length of dental implants may be a critical factor in achieving and maintaining osseointegration. Purpose: The aim of this study was to evaluate the survival rate and bone loss of dental implants with different lengths Materials and Methods: A retrospective cohort study was performed on 60 ITI-system implants, evenly distributed into three groups including 8, 10 and 12 mm high implants in the posterior segments of both jaws. Demographic information, oral hygiene, cigarette smoking, implant length, duration of implant placement (at least 24 months), bleeding on probing index and pocket probing depth were recorded for all participants. Bone loss was calculated using pre- and post-operative panoramic radiographs. Results: The mean rate of bone loss was different among the three groups and were found to be 0.21 (0.45), 0.3 (0.41) and 0.43 (0.55) mm in the 8, 10, and 12 mm high implants, respectively. Neither mean bone loss nor bleeding on probing index showed significant differences with implant length. A significant correlation was found between implant length and pocket probing depth (P